'They care rudely!': resourcing and relational health system factors that influence retention in care for people living with HIV in Zambia. Issue 5 (25th October 2018) - Mwamba, Chanda; Sharma, Anjali; Mukamba, Njekwa; Beres, Laura; Geng, Elvin; Holmes, Charles B; Sikazwe, Izukanji; Topp, Stephanie M
Abstract : Introduction: Despite access to free antiretroviral therapy (ART), many HIV-positive Zambians disengage from HIV care. We sought to understand how Zambian health system 'hardware' (tangible components) and 'software' (work practices and behaviour) influenced decisions to disengage from care among 'lost-to-follow-up' patients traced by a larger study on their current health status. Methods: We purposively selected 12 facilities, from 4 provinces. Indepth interviews were conducted with 69 patients across four categories: engaged in HIV care, disengaged from care, transferred to another facility and next of kin if deceased. We also conducted 24 focus group discussions with 158 lay and professional healthcare workers (HCWs). These data were triangulated against two consecutive days of observation conducted in each facility. We conducted iterative multilevel analysis using inductive and deductive reasoning. Results: Health system 'hardware' factors influencing patients' disengagement included inadequate infrastructure to protect privacy; distance to health facilities which costs patients time and money; and chronic understaffing which increased wait times. Health system 'software' factors related to HCWs' work practices and clinical decisions, including delayed opening times, file mismanagement, drug rationing and inflexibility in visit schedules, increased wait times, number of clinic visits, and frustrated access to care. While patients considered HCWs as 'mentors' and trusted sources of information, many also described them as rude, tardy, careless with details and confidentiality, and favouring relatives. Nonetheless, unlike previously reported, many patients preferred ART over alternative treatment (eg, traditional medicine) for its perceived efficacy, cost-free availability and accompanying clinical monitoring. Conclusion: Findings demonstrate the dynamic effect of health system 'hardware' and 'software' factors on decisions to disengage. Our findings suggest a need for improved: physical resourcing and structuring of HIV services, preservice and inservice HCWs and management training and mentorship programmes to encourage HCWs to provide 'patient-centered' care and exercise 'flexibility' to meet patients' varying needs and circumstances.